The sharp quantitative Sobolev inequality for functions of bounded variation - Fusco, Nicola; Maggi, Francesco; Pratelli, Aldo (Journal of Functional Analysis, 2007)
The classical Sobolev embedding theorem of the space of functions of bounded variation BV(R-n) into L-n' (R-n) is proved in a sharp quantitative form. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Sobolev inequality; BV functions; sharp estimate; isoperimetric inequality